Parameters by Spatial and Temporal Methods of Different Types of Phytoplankton in the Waters of Jakarta Bay - Munawir, Abdillah -; Anwar, Kasful (Jurnal Penelitian Perikanan Indonesia, 2024)
This study aims to determine the spatial and temporal variability of physical, chemical, biological aquatic parameters in Jakarta Bay. Experimental research methods are supported by spatial and temporal methods with calculation of physical parameters such as flow velocity, calculation of chemical parameters such as N, P, Silica, salinity, Dissolved organic nitrogen, Orthophosphate and amount of iron content in Jakarta Bay. As for the calculation of biological parameters in the form of abundance of phytoplankton communities. The results of the analysis of the spatial and temporal variability of the physical, chemical and biological parameters of the waters in Jakarta Bay have an influence on the development of phytoplankton communities in the waters. Changes in concentration and N:P ratio led to an explosion of phytoplankton populations of certain types in the waters of Jakarta Bay. Biological variability of phytoplankton types found to dominate phytoplankton communities in Jakarta Bay Waters are the genera Skeletonema, Chaetoceros, and Rhizosolenia.